Modeling of nuclear reactor core for power control simulation with temperature feedback and xenon concentration effect - Djarouma Bélaid- Mohammedia Boussaad -Abderrahmane Khelilb-Laouara Sofiane (University of Eloued جامعة الوادي, 2023)
Modeling nuclear reactor cores stands as an essential initial step in nuclear technology research and development. The reactor core, serving as the primary thermal energy source in nuclear power plants (NPPs), plays a pivotal role. Such reactor core modeling serves various objectives, including core power control and load-following operations within NPPs. In this study, the pressurized water reactor (PWR) core was modeled using the point reactor method, a technique widely applied in conjunction with multiple reactor core power control strategies during load-following operations. Employing a proportional-integral-derivative (PID) controller, load-following scenarios tailored to grid load maneuvers were implemented in the developed reactor core model. The study also delved into the effects of temperature feedback and xenon. The analysis of simulation results revealed only a very small deviation in power between the desired and actual reactor core power. A substantial movement of the control rods effectively countered the notable impact of xenon on reactor power. Regarding temperature feedback, its contribution to the core total réactivity with a negative reactivity was confirmed. This study utilized the Python language for both the development of the nuclear reactor model and the creation of algorithms required for power control during load-following mode. Typically, similar endeavors with distinct objectives are conducted using MATLAB SIMULINK
Article
Keywords: Modeling; Nuclear reactor; Power control; PID; Python Algorithms.